Compact fractal interferometers for a 4‐bit IFM system. Issue 5 (27th March 2017) - Silva, C.P.N.; Machado, G.G.; de Oliveira, E.M.F.; de Oliveira, M.R.T.; de Oliveira, B.G.M.; de Melo, M.T.
ABSTRACT: Instantaneous frequency measurement (IFM) systems have been developed during the last decades, and new designs came across trying to keep the system as compact as possible. In this paper, the authors present compact interferometers based on Hilbert fractal geometry for a 4‐bit IFM system. The interferometers operate in the range 4.66–6.38 GHz, using a Wilkinson power divider connected to two microstrip lines, which one of these is the Hilbert fractal curve. The design and simulations to be presented were done in a full wave EM simulator. Measured and simulating results are presented and compared. © 2017 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:1153–1157, 2017